Detection and Neutralization of SARS-CoV-2 Using Non-conventional Variable Lymphocyte Receptor Antibodies of the Evolutionarily Distant Sea Lamprey - Leung, Leslie Y. T.; Khan, Srijit; Budylowski, Patrick; Li, Zhijie; Goroshko, Sofiya; Liu, Yanling; Dong, Shilan; Carlyle, James R.; Rini, James M.; Ostrowski, Mario; Ehrhardt, Götz R. A. (Frontiers in Immunology, 2021)
SARS-CoV-2 is a newly emerged betacoronavirus and the causative agent for the COVID-19 pandemic. Antibodies recognizing the viral spike protein are instrumental in natural and vaccine-induced immune responses to the pathogen and in clinical diagnostic and therapeutic applications. Unlike conventional immunoglobulins, the variable lymphocyte receptor antibodies of jawless vertebrates are structurally distinct, indicating that they may recognize different epitopes. Here we report the isolation of monoclonal variable lymphocyte receptor antibodies from immunized sea lamprey larvae that recognize the spike protein of SARS-CoV-2 but not of other coronaviruses. We further demonstrate that these monoclonal variable lymphocyte receptor antibodies can efficiently neutralize the virus and form the basis of a rapid, single step SARS-CoV-2 detection system. This study provides evidence for monoclonal variable lymphocyte receptor antibodies as unique biomedical research and potential clinical diagnostic reagents targeting SARS-CoV-2.